The Pieniny Klippen Belt in Poland - Golonka, Jan; Krobicki, Michał; Waśkowska, Anna (Geology, Geophysics and Environment, 2018)
The Pieniny Klippen Belt in Poland marks the Central Carpathian-North European plate suture zone. The strictly tectonic present-day confines of the Pieniny Klippen Belt are characterized as (sub)vertical faults and shear zones. A strong reduction in the space of the original sedimentary basins took place. The strike-slip-bounded tectonic blocks, thrust units, toe-thrusts and olistostromes are mixed together, resulting in the present-day mélange character where individual tectonic units are difficult to distinguish. The sedimentary rocks of the Pieniny Klippen Belt were deposited in the paleogeographic realm known as the Alpine Tethys that was divided into two basins separated by the Czorsztyn Ridge. The accretionary prism formed in front of the advancing Alcapa (Central Carpathians) terrane had overridden the Czorsztyn Ridge during the Late Cretaceous-Paleocene. The destruction of the Czorsztyn Ridge supplied huge amounts of coarse-clastic material, including olistoliths, into the Magura Basin during the Late Cretaceous-Paleocene. The rotation of the Alcapa caused the strike-slip motions which led to the deformation of the previously created nappes and development of the flower structure. Two parallel faults delineate the southern and northern limits of the Pieniny Klippen Belt. The stops in Sromowce (Macelowa and Sobczański Gorge area) allow the observation of the southern marginal zone of the Pieniny Klippen Belt, the overturned position of the rotated counterclockwise deformed rock as well as the diapiric uplift of the Pieniny rocks in a transpressional strike-slip regime. The Zawiasy (Krościenko area) stop is located in the northern marginal zone (Hulina Unit) of the Pieniny Klippen Belt along the major dextral strike-slip Dunajec Fault.